An evaluative study of the effectiveness of content-based instruction as an EFL approach in China’s tertiary education - Wang, Ping (2018)
In the 21st-Century China, ELT has been constantly promoted because of such events as China’s entry into the WTO in 2001, hosting the Beijing Olympic Games in 2008,and the One Belt,One Road Initiative by President Xi Jinping in 2013. These have beengreat opportunities for universities in China to demonstrate their value in contributing to the nurturing of the “international talents” in the socio-political and academic discourses in China (Feng, 2010; 2017). In the past decade, content-based instruction (CBI),which seems to resonate strongly with goals of educating the “international talents”, has become increasingly popular in tier-2 university EFL contexts. The present study as its title indicates is an evaluative study of the effectiveness of CBI as an EFL approach in a tier-2 university, holistically, aiming to examine the effectiveness of CBI on its potential with regard to English attainment and progress, attitudes and motivation, and engagement with authentic literature. It also aims to obtain an in-depth understanding of whether CBI could be an alternative to traditional College English (CE) teaching at a higher level. The samples chosen were a cohort of CBI learners who had passed CET 4 (College English Test, Band 4) at a typical tier-2 university in China. To achieve the overall aim of this study, mixed methods were employed in this research. Given the research context, 200 subjects (aged 18-22 years) were chosen, who were readily available in five intact 2nd year CBI classes of the fivemajors. Of the 200 participants, 52% (104) were female and 48% (96) were male. They were asked to complete two questionnaire surveys, and three tests. The subjects for the qualitative instruments were chosen among those who had responded to the questionnaires. 20 of the students were selected for semi-structured individual interviews.Among the 20 interviewees, 11 were female and nine male. Ten students (half female and half male) were selected from the CBI classes for focusgroup interviews. Interviews with five content specialists as CBI teachers were conducted, and their classes were observed twice. Among the five CBI teachers, 2 were female, and 3 male. The class size ranged between 37 and 45 students. Iterative data analyses were conducted to process the data collected to guarantee a triangulating examination with regard to the effectiveness of the CBI program in the tier-2university EFL context. The overall conclusion is drawn that CBI in the tier-2 university EFL context is an effective way to develop non-English majors’ English proficiency, as compared to traditional CET-oriented teaching, and more significantly to enhance the learners’ attitudes and motivation to English teaching, and engagement with authentic texts. It is noted that CBI can have its advantage over CE for students with a CET 4 certificate in the tier-2 university EFLcontext, but some conditions such as qualified tutors and strong policy support should be satisfied. Implications and limitations are discussed, and future areas of investigation are put forward.